Dampak Faktor Pajak dan Profitabilitas Terhadap Tingkat Hutang: Studi Empiris pada Perusahaan-Perusahaan yang Tergabung Dalam Indeks Kompas-100 di Bursa Efek Indonesia - Hiong, Lauw Sun (MABIS, 2011)
The aim of this research is to analyze the influence of Corporate Tax Ratio (CTR), Non Debt Tax Shield (NDTS), and Profitability (PR) variables against Leverage (LV) on the companies incorporated in kompas-100 index and listed in Indonesia Stock Exchange for period 2009-2011. The research employs a method of purposive sampling for sampling. Data â collected from 41 companies sampling â is obtained with a basis of Indonesian Capital Market Directory (ICMD) publication. The analysis technique employed is multiple regression analysis. With a basis of F statistic test, it indicates that both models meet fit criteria for their value of significance being less than 5% in a real rate. While t statistic-based test indicates that the corporate tax ratio (CTR) of the companies brings negative impact and is not significant against the policy of debt (Leverage) and this is proven from its value of significance being less than 5% in a real rate. Meanwhile Non Debt Tax Shield has positive and significant influence against the policy of debt (leverage) which is proven from its value of significance being less than 5% in a real rate. While profitability variable has a negative and significant influence, in line with the hypothesis formulated by the author, with a value of significance being less than 5% in real rate. The analysis results showed the significance of predictive ability of the three independent variables, such as Corporate Tax ratio, Non Debt Tax Shield, and profitability against policy of debt being at a rate of 11.6% indicated from the adjusted R2, the rest of which is as much as 88.4% being influenced by other variables beyond the model.